Analysis of Data on Adverse Drug Reactions and Functional Flaws of the Pharmacovigilance System Associated with Self-Treatment with Antibiotics - N. V. Verlan; T. L. Moroz; E. O. Kochkina; E. N. Bochanova; E. A. Beigel (Безопасность и риск фармакотерапии)
In the Russian Federation, a substantial proportion of the population (39.3–75.7%) opts for self-treatment. Self-administration of prescription medicinal products, particularly antibiotics, can lead to serious adverse drug reactions (ADRs). The safety of medicines in circulation relies upon the proper functioning of the pharmacovigilance system, both in general and in the case of self-medication ADRs.The aim of the study was to analyse data on the serious ADRs attributed to self-treatment with antibiotics and reported to the Regional Centre for Drug Safety Monitoring of the Irkutsk Region, as well as on the pharmacovigilance problems associated with self-treatment.Materials and methods: the study analysed the suspected ADR reporting forms from the database accumulated by the Regional Centre for Drug Safety Monitoring of the Irkutsk Region in 2011–2019. The inclusion criteria for the reporting forms were full completion and a Naranjo probability score categorising antibiotic–ADR causality at least as “possible”.Results: of the total 2325 reports in the database, 790 (34%) were on the ADRs associated with the use of antibiotics. Of these, 222 reported serious ADRs caused by self-medication. The largest number of ADRs (126) was recorded in patients aged 40–70 years; the proportion of women (60.32%) was significantly higher than the proportion of men (39.68%). Hospitalisation was required for 23 patients with serious adverse events. In 80% of the studied cases, patients justified the need for self-prescription of antibiotics with cough (which they regarded as acute bronchitis), but their presumptive diagnosis coincided with that established in the hospital only in 47.83% of the cases. The reports of ADRs during self-treatment with antibiotics were mainly received from hospitals (205 cases), and much less often from outpatient clinics and directly from patients (9 and 8 cases, respectively). There were no reports from pharmacy organisations; and it may be assumed that their employees did not take active part in reporting.Conclusions: the use of antibiotics for self-medication can lead to serious ADRs; therefore, the medicinal products of this class should be used only as directed by a doctor. To reduce the incidence of ADRs, it is necessary to raise awareness of the population and medical specialists conducting antibiotic therapy. The quality of medical care will benefit from proper performance of pharmacovigilance activities by all parties to the circulation of medicines, active involvement of patients in treatment safety monitoring, inclusion of specific sections on practical functioning of the pharmacovigilance system into the training curricula of pharmaceutical professionals, and creation of a feedback system connecting pharmacovigilance organisations to medical ones and other subjects of the circulation of medicines.